An Operational Framework for the Advancement of a Molecule-to-Biosphere Stoichiometry Theory - Cherif, Mehdi; Faithfull, Carolyn; Guo, Junwen; Meunier, Cédric L.; Sitters, Judith; Uszko, Wojciech; Rivera Vasconcelos, Francisco (Frontiers in Marine Science, 2017)
Biological stoichiometry is an approach that focuses on the balance of elements in biological interactions. It is a theory that has the potential to causally link material processes at all biological levels – from molecules to the biosphere. But the lack of a coherent operational framework has so far restricted progress in this direction. Here, we provide a framework to help infer how a stoichiometric imbalance observed at one level impacts all other biological levels. Our framework enables us to high the areas of the theory in need of completion, development and integration at all biological levels. Our hope is that this framework will contribute to the building of a more predictive theory of elemental transfers within the biosphere, and thus, to a better understanding of human-induced perturbations to the global biogeochemical cycles.